(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
It is studied the predictive structure of frustration states of pupils of different age groups. The emphasis is placed on the importance in this structure the accentuations of personality, which are considered as potential determinants of the emergence of frustration states. There are presented the results of experimental study of personality accentuations and their correlation with frustration reactions of pupils of different age groups (younger schoolchildren, teenagers, young men).